First report of Rhizoctonia solani causing Banded leaf and sheath blight disease in Sugarcane (Saccharum officinarum) from Ghazipur district of Uttar Pradesh, India - MALVIYA, DEEPTI; SINGH, SHAILENDRA; SINGH, RAJIV K; RAI, JAI P; SINGH, UDAI B; SAXENA, A K (The Indian Journal of Agricultural Sciences, 2022)
During August 2016, banded leaf and sheath blight symptoms were observed on sugarcane (cv. BO-91) in the Village Bhawanipur of Ghazipur district of Uttar Pradesh (India). A survey was done to assess the prevalence of and collect the specimens of banded leaf and sheath blight disease from sugarcane fields in the Ghazipur district during 2016–17. A total of 15 fungal isolates were collected from different parts of the district and pathogenicity testing of these isolates was done following Koch postulates. All the 15 isolates were able to produce disease in the controlled laboratory conditions as well as in the field. Further, these isolates were morphologically characterized as Rhizoctonia solani. To confirm the identity at molecular level, ITS sequencing of two most virulent isolates was done. Based on the ITS sequence similarity, these two isolates, viz. SCRS-2018-1A and SCRS-2018-1B were identified as R. solani. As per the existing records and our knowledge based on the extensive survey of pertinent literature, this is the first report of R. solani causing banded leaf and sheath blight disease in Sugarcane from Ghazipur district of Uttar Pradesh, India.